Review on The Effect of Zinc Salt on Performance of Polysulfone Material. - Abdul Ghafar, Ahmad Azfar Zuhri; Yunos, Muhamad Zaini (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This project was conducted to identify the reaction of additive material due to lack of performances of Polysulfone (PSF) and to improve the Polysulfone membrane and the reason used of this non-solvent addictive because the low cost and dilute insolvent. This project aims to improve the Polysulfone membrane by using an addictive’s material and this study aims to investigate the effect of non-solvent addictive on Polysulfone membrane and to characterize the mechanical behaviour, physical, and also membrane performance of prepared material. In this study, the experiments work to determine the Polysulfone membrane by using Zinc Chloride, Zinc Acetate, and Zinc Nitrate. The concentration will be varied from 0-5% and the result showed the mechanical properties will be enhance due to increases of zinc salt. The results for physical of the Polysulfone membrane showed decreases in contact angle and rose in porosity. This results for the performance of the membrane by its permeability and rejection also increases, and fouling will be minimize.